Взаємовідносини Національної поліції та громади під час воєнного стану - Новіченко, А. В.; Novichenko, A. V. (Право.ua. - 2024. - № 1. - С. 86-93, 2024)
Досліджено взаємовідносини між Національною поліцією та громадою під час воєнного стану. Сучасні реалії, а саме збройна агресія та напад на Україну з боку збройних сил Російської Федерації, зумовили впровадження воєного стану на всій території держави та внесення змін до чиного законодавства України. Ці зміни також торкнулись правоохоронної діяльності. Введення режиму воєнного стану обумовлено особливою увагою з боку держави, щодо аспектів взаємодії правоохоронних органів, зокрема поліції, із громадськими об’єднаннями, окремими громадянами з питань охорони громадського порядку, розбудови партнерської моделі взаємин між ними в умовах воєнного стану.

The large-scale invasion of the territory of Ukraine by the armed forces of the Russian Federation is aimed at a real threat to state sovereignty, territorial integrity, the democratic constitutional system and other national interests of the state. The armed attack of the Russian troops led to the introduction of martial law in Ukraine, which is aimed at the unification and interaction of not only state bodies, such as the Armed Forces of Ukraine, the National Police, the National Guard, local state administrations, but also local self-government bodies, territorial communities and citizens, with the aim of resisting the destruction of the state of Ukraine. The armed attack of the aggressor country caused special attention on the part of the state, which must be paid to aspects of the interaction of law enforcement agencies, in particular the police, with public associations, citizens on matters of public order protection, development of a partnership model of relations between them under martial law.

Исследованы взаимоотношения между Национальной полицией и общиной во время военного положения. Современные реалии, а именно вооруженная агрессия и нападение на Украину со стороны вооруженных сил Российской Федерации, обусловили введение военного положения на всей территории государства и внесение изменений в действующее законодательство Украины. Эти изменения также затронули правоохранительную деятельность. Введение режима военного положения обусловлено особым вниманием со стороны государства относительно аспектов взаимодействия правоохранительных органов, в частности полиции, с общественными объединениями, отдельными гражданами по вопросам охраны общественного порядка, развития партнерской модели взаимоотношений между ними в условиях военного положения.
Relations between the National Police and the community during martial law
Keywords: Національна поліція України; правоохоронні органи; громада; взаємодія поліції з населенням; воєний стан; громадяни; National Police of Ukraine; law enforcement agencies; community; interaction of the police with the population; martial law; citizens; Национальная полиция Украины; правоохранительные органы; община; взаимодействие полиции с населением; военное положение; граждане